The Effectiveness of Programmatic Advertising Compared to the Classical Display Advertising : The Case of ABRA Software - Vondrák, František (2023)
Display advertising represented approximately 50% of the overall online advertising spend, making it, if not the most critical channel for building brand awareness and generating leads. This thesis thus aims to find out which one of the two most popular technologies used for display advertising – programmatic and Google Display Network is more effective at delivering better digital marketing performance metrics. As a means to do so, various digital marketing metrics are examined and compared in the case of a Business-to-Business (B2B) company in the context of the Software-as-a-Service (SaaS) industry. These performance metrics are analyzed through two experiments constructed by the author. Experiment one is based on first-party data from Google and Adform. Experiment two builds upon first-party data from the company's income of leads reports. The findings suggest that within the examined period, Google Display Network performed better at cost-per-mille (CPM), clicks, cost-per-click (CPC), and click-through-rate (CTR), whereas programmatic delivered better results at Impressions, leads generated, and income generated by leads. Having analyzed the trendlines, programmatic should outperform Google Display Network in all the performance metrics in the long run, however. In order to choose the most effective digital advertising technology, businesses should account for their individual digital marketing goals.